EFEKTIVITAS PROGRAM RIAU CREATIVE CENTER (RCC) BIDANG EKONOMI KREATIF OLEH DINAS PARIWISATA PROVINSI RIAU - M. Putra Geramezio; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Riau Creative Center (RCC) program is a program created by the Riau Provincial Tourism Office with the aim of sharing information about the activities of creative economy actors with the wider community and providing economic added value and creating a source of regional income. The purpose of this study is to find out how effective the RCC program is in its implementation in the field and its inhibiting factors. The theoretical concepts used in this study are effectiveness theories consisting of: Achievement of Goals, Integration, and Adaptation. This research is a qualitative research with a case study approach. The selection of informants in this study uses purposive sampling technique. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the RCC program in the creative economy has been carried out but not yet running optimally. This is due to inhibiting factors in the implementation of the program which include internal factors and external factors. It is recommended that the Riau provincial tourism office through the Creative Economy sector be responsible for the RCC program so that it pays more attention to the program goals and objectives that have been previously determined and evaluates the programs that have been carried out.Keywords :  Effectiveness, Creative Economy, RCC Program.